Measurement of Fisherman Terms of Trade before and after The Covid-19 pandemic at Parit Baru Village, Salatiga sub-district (Agrikan Jurnal Agribisnis Perikanan, 2022)
Terms of Trade Fisherman focuses on the income and expenditure of fishermen's families with the aim of seeing the level of fishermen's welfare. The purpose of the study was to see the trend of NTN before and after the Covid-19 pandemic. Descriptive quantitative research method with a non-probability sampling method of determining samples and purposive sampling as a sampling technique with a questionnaire as a tool while in-depth interviews. The results of the study were 20 fishermen (before Covid-19) & 22 fishermen (after Covid-19) with NTN < 1, NTN = 1 as many as 3 fishermen (before Covid-19) & 0 fishermen (after Covid-19, NTN > 1 as many as 2 (before Covid-19) & 3 fishermen (after Covid-19). On average, NTN before Covid-19 was 1.0 and 0.9 after Covid-19, meaning fishermen have not been able to meet their primary needs.
Keywords: Pari Baru Village; Terms of Trade Fisherman; Covid-19; Fisherman’s Welfare, Trend